2020
DOI: 10.1080/21645515.2020.1747375
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of influenza vaccine in elderly people: a systematic review and meta-analysis of randomized controlled trials, and its association with real-world effectiveness

Abstract: Background: Older people (≥60 years old) are particularly vulnerable to influenza virus infection, and vaccine is effective in reducing the disease burden in this population. However, it remains obscure whether their antibody response is lower than those of younger adults (18-60 years old). Thus, this meta-analysis was performed to compare the immunogenicity of influenza vaccines and understand their association with real-world vaccine effectiveness (VE) between these two age groups. Methods: A systematic lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
2
11
0
3
Order By: Relevance
“…A systematic review and meta-analysis concluded that the seroprotection rate (SPR) and seroconversion rate (SCR) of older adults for A/H1N1 and B/Victoria were lower than those of younger adults, whereas the two age groups had similar antibody responses for A/H3N2 [ 24 ].…”
Section: Main Textmentioning
confidence: 99%
“…A systematic review and meta-analysis concluded that the seroprotection rate (SPR) and seroconversion rate (SCR) of older adults for A/H1N1 and B/Victoria were lower than those of younger adults, whereas the two age groups had similar antibody responses for A/H3N2 [ 24 ].…”
Section: Main Textmentioning
confidence: 99%
“…Os sinais e sintomas nos pacientes, no início de ambas as patologias, SARS e MERS, são febre, mialgia, fadiga, tosse e em grande parte dos pacientes, dispneia. A presença de diarreia, dor de cabeça, tosse com sangue e escarro, são menos comuns (HUANG et al, 2020;GUAN et al 2020;WANG et al, 2020) 2020).…”
Section: Biossegurança Na Odontologia Antes Da Pandemia Covd-19unclassified
“…Isso explica a grande ênfase das autoridades sanitárias para que as mãos sejam lavadas e/ou desinfetadas com álcool gel 70%, evitando que caso elas sejam levadas aos olhos, contaminem o paciente (HUANG et al 2020).…”
Section: Classificação De Risco Nosocomialunclassified
“…The presence of antibodies directed against the HA glycoprotein on the virus surface which is subject to substantial immune selection pressure is considered the principal reference for protection against influenza viruses. However, vaccination strategies targeting influenza surface glycoproteins frequently have suboptimal effectiveness due to 1) virus mismatches ( 2 , 3 ) and 2) low humoral responses in fragile populations ( 4 ). Nonetheless, CD8+ cytotoxic T-cells also play a role in the mechanisms that protect against influenza ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%